2011
DOI: 10.1159/000329478
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Cytogenetic and Molecular Study in a Case of r(3) with 3p Deletion and Review of the Literature

Abstract: Ring chromosome 3 is a rare abnormality with only 10 patients described in the literature. We report a patient with r(3) and ∼6-Mb distal 3p deletion. Single nucleotide polymorphism array, multiplex ligation-dependent probe amplification and fluorescence in situ hybridization techniques revealed that the ring was formed by a break in 3p26.1 and fusion with the subtelomeric region of 3q. The patient presents delayed psychomotor development, growth failure, minor anomalies and other features similar to patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Our patient shared some of the phenotypes found in other patients with r(3) and 3p deletion syndrome, such as growth failure, developmental delay, mental retardation, microcephaly, dysmorphism, and ptosis as well as an additional CHD which has not been observed in r(3) patients but has been reported in about 30% of patients with 3p deletion syndrome [Shuib et al, 2009;Guilherme et al, 2011a]. The 3p deletion syndrome is a contiguous gene syndrome caused by deletions of variable lengths of the 3pterp25 region that is rather well defined since it was first reported in 1978 and has some common features with r(3), despite the low number of reported cases [Kitatani et al, 1984;Teyssier et al, 1991;Malmgren et al, 2007;Pohjola et al, 2010;Guilherme et al, 2011a;Kaur and Khetarpal, 2013].…”
Section: B)supporting
confidence: 83%
See 3 more Smart Citations
“…Our patient shared some of the phenotypes found in other patients with r(3) and 3p deletion syndrome, such as growth failure, developmental delay, mental retardation, microcephaly, dysmorphism, and ptosis as well as an additional CHD which has not been observed in r(3) patients but has been reported in about 30% of patients with 3p deletion syndrome [Shuib et al, 2009;Guilherme et al, 2011a]. The 3p deletion syndrome is a contiguous gene syndrome caused by deletions of variable lengths of the 3pterp25 region that is rather well defined since it was first reported in 1978 and has some common features with r(3), despite the low number of reported cases [Kitatani et al, 1984;Teyssier et al, 1991;Malmgren et al, 2007;Pohjola et al, 2010;Guilherme et al, 2011a;Kaur and Khetarpal, 2013].…”
Section: B)supporting
confidence: 83%
“…It is reported that most patients with a ring chromosome displayed ring instability [Guilherme et al, 2013]. A ring chromosome is considered unstable when it produces secondary aberrations in more than 5% of cells [Kosztolányi et al, 1987;Guilherme et al, 2011a]. The unstable r(3) was observed in our patient with ring instability in 9.67% of the cells.…”
Section: B)mentioning
confidence: 50%
See 2 more Smart Citations
“…4,5 This chromosomal abnormality is associated with prenatal and postnatal growth deficiency, cognitive impairment, distinctive craniofacial malformations, synophrys, and hypertrichosis. 6 The following ophthalmic associations have been reported: ptosis, iris coloboma, upward-slanting eyelids, and wide-set eyes.…”
Section: Discussionmentioning
confidence: 99%